Genitoanal Injury in Sexually Assaulted Adult Women: Six-Year Retrospective in Bangkok - Papanu Suttipasit (2019)
© Wolters Kluwer Health, Inc. All rights reserved. Sexual assault persists as a global problem. Even when sexual assault does not result in obvious visible wounds, genitoanal injury must be evaluated because it is often pertinent for legal outcomes. Macroscopic ("naked eye") examination is valuable when colposcope is not available or when patients do not consent. This study reviewed the genitoanal injuries of 117 sexually assaulted adult women evaluated macroscopically. Genitoanal injury prevalence was 47%, and nongenitoanal injury prevalence was at 44%. The most common injury type was abrasion, and the most common site was posterior fourchette. Most injury patterns were singular. The number of women who did not report a history of sexual intercourse in the sample and usage of fingers/palm during assault may have affected pattern and/or injury type. There was a significant relationship between hymenal old tear below the 3- to 9-o'clock area and prior sexual intercourse. Factors related to genitoanal injury were prior sexual intercourse, vaginal delivery, and spermatozoa detection. In conclusion, all sexually assaulted women should be encouraged to have a pelvic examination: nothing overtly visible does not mean that nothing happened.